2013
DOI: 10.2298/vsp110713035k
|View full text |Cite
|
Sign up to set email alerts
|

Body weight and waist circumference as predictors of vitamin D deficiency in patients with type 2 diabetes and cardiovascular disease

Abstract: The high prevalence of vitamin D deficiency in patients with T2DM and particularly in patients with T2DM and CVD suggests that supplementation with vitamin D may be beneficial although there is still not sufficient evidence for recommending prescribing vitamin D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…In addition, extended socioeconomic transition corresponded to high prevalence of other common chronic diseases, which additionally affected community health status in an adverse direction (21). It has been recently demonstrated that markers of nutritional pattern relating to obesity represented a strong predictor for vitamin D deficiency in patients with chronic, metabolic disease (22). Other researchers in Serbia found that the mean serum concentrations of 25-hydroxyvitamin D were much below the threshold in an apparently healthy (student) population (23).…”
mentioning
confidence: 99%
“…In addition, extended socioeconomic transition corresponded to high prevalence of other common chronic diseases, which additionally affected community health status in an adverse direction (21). It has been recently demonstrated that markers of nutritional pattern relating to obesity represented a strong predictor for vitamin D deficiency in patients with chronic, metabolic disease (22). Other researchers in Serbia found that the mean serum concentrations of 25-hydroxyvitamin D were much below the threshold in an apparently healthy (student) population (23).…”
mentioning
confidence: 99%
“…Eleven studies covering 2236 patients and 2438 controls were employed to metaanalyze the 25(OH)D levels in T2D patients . Six studies were conducted in Asia, and five in Europe.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the exclusion of the two studies by Al‐Daghri et al. also changed the summary SMD largely (Fig. B), which should result from the observed relatively higher vitamin D levels in T2D patients than controls in the two studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the indirect indicators of visceral adipose tissue is considered to be the waist circumference (WC). In a systematic review (17 prospective and 35 cross-sectional studies reviewed) published in 2010, it was reported that the ratio of BMI, WC and WC/hip circumference could predict diabetes risk independently of each other [11]. BMI is considered to have less sensitivity than WC [12].…”
Section: Introductionmentioning
confidence: 99%